Vagus nerve stimulation in a pediatric population: Surgical technique considerations - Awaad, Yasser; Rizk, Tamer; Roosen, Norbert; Mcintosh, Kelly A.; Waines, Michael (Journal of Pediatric Neurology, 2011)
During the past decade, vagus nerve stimulation has become an accepted treatment method for patients with refractory epilepsy who are not proper candidates for invasive, potentially curative epilepsy surgery such as lesionectomy or mesial temporal lobectomy. We aimed to review our clinical experience with vagus nerve stimulation in a pediatric and young adolescent population specifically focusing on the necessary special considerations for these young patients and on surgical pearls in this age group. This is a single center study from the Oakwood Hospital Epilepsy Clinic in which all our consecutively enrolled patients were followed as a cohort with ongoing concurrent as well as retrospective review of in-patient and outpatient records. All patients (n = 30) had a technically successful initial implantation procedure, but four (13%) required additional interventions. This included six revisions for mechanical causes, pectoral dehiscence and explants as well as re-implantation. Epilepsy control improved remarkably in 20 patients (67%) resulting in an improved quality of life for the majority of our patients. Appropriate technical modification and attention to detail is needed in these young patients to achieve optimal surgical results.
Keywords: Vagus nerve stimulation; child; surgery; complication; epilepsy; seizures